Common species of Cyclorraphan Diptera in a Red Junglefowl Farm, Selangor, Malaysia - Ibrahim, Nor Hidayah; Babjee, Shaik Mohamed Amin; Kumar Sharma, Reuben Sunil (2012)
A study on the prevalence of Cyclorrhaphan Diptera species was carried out in a Red Jungle Fowl Farm, Dengkil, Selangor, Malaysia. Trappings were done twice a day, in the morning and evening, using hand nets and baited traps over a duration of 7 days. Chicken intestines were used as bait to attract the flies. The mean temperature and relative humidity during the period of sample collection were recorded. The flies were counted and the identification of species was based on standard taxonomic keys. Eleven species of flies were detected on the farm, representing eight genera; Chrysomya megacephala, Chrysomya rufifacies, Lucilia cuprina, Hemipyrellia liqurriens, Musca domestica, Musca sorbens, Musca ventrosa, Parasacrophaga, Boettcherisca, Seniorwhitea princeps and Chrysomela cf. aenea. The most prevalent fly species was Chrysomya megacephala, accounting for 80% of the total catch, followed by Musca domestica (5.15%). The other species were present in less than 5% of the catch. There was no significant correlation between temperature and the active fly population (r=-0.324, n=14, p=0.258). Similarly, the relative humidity did not have a significant effect on the number of flies on the farm (r=0.257, n=14, p=0.376). The number of female flies on the farm was high, comprising 64.42% of the total fly population. Certain species of flies displayed temporal activity. Chrysomyza cf. aenea and Seniorwhitea princeps were active in the morning, while Boetcherisca sp. was only encountered in the evening. The correct identification of the fly species, and knowledge on their temporal distribution and sex ratios, are important in order to ensure that control measures can be carried out in a more effective manner.